Interrelationship Between Obstructive Sleep Apnea Syndrome and Severe Asthma: From Endo-Phenotype to Clinical Aspects - Ragnoli, Beatrice; Pochetti, Patrizia; Raie, Alberto; Malerba, Mario (Frontiers in Medicine, 2021)
Sleep-related breathing disorders (SBDs) are characterized by abnormal respiration during sleep. Obstructive sleep apnea (OSA), a common SBD increasingly recognized by physicians, is characterized by recurrent episodes of partial or complete closure of the upper airway resulting in disturbed breathing during sleep. OSA syndrome (OSAS) is associated with decreased patients' quality of life (QoL) and the presence of significant comorbidities, such as daytime sleepiness. Similarly to what seen for OSAS, the prevalence of asthma has been steadily rising in recent years. Interestingly, severe asthma (SA) patients are also affected by poor sleep quality—often attributed to nocturnal worsening of their asthma—and increased daytime sleepiness and snoring compared to the general population. The fact that such symptoms are also found in OSAS, and that these two conditions share common risk factors, such as obesity, rhinitis, and gastroesophageal reflux, has led many to postulate an association between these two conditions. Specifically, it has been proposed a bidirectional correlation between SA and OSAS, with a mutual negative effect in term of disease severity. According to this model, OSAS not only acts as an independent risk factor of asthma exacerbations, but its co-existence can also worsen asthma symptoms, and the same is true for asthma with respect to OSAS. In this comprehensive review, we summarize past and present studies on the interrelationship between OSAS and SA, from endo-phenotype to clinical aspects, highlighting possible implications for clinical practice and future research directions.